Economic effects of advertising - Mendoza Henríquez, Miguel R.; Muñoz C., Juan P. (Estudios de Administración, 1994)
This paper analyzes the role of advertising within the social system. The first part discusses the social consequences in terms of consumer manipulation values, beliefs and life style of consumers. An analysis is performed of the economic effects of advertising, by testing the hypothesis that advertising has positive effects on economic decisions made by companies and consumers.